L’Educazione musicale nelle "Indicazioni per il curricolo": tra esperienza, produzione, ascolto - Somigli, Paolo (Musica Docta, 2012)
The article starts from a reflection about the concept of “experience” in XXth-Century Pedagogy; on this basis, it discusses some aspects of the Indicazioni per il curricolo (2007), with special care to the problem of the musical genres, music listening and the production; then it underlines the importance of offering to children new musical experience, paying special attention to the role of the music of art in music education.